Istana Siak Sri Indrapura: Warisan Sejarah dan Budaya Melayu di Riau - Putra, Gilang Syahrulka; Pama, Sindi Ayudia (Green Publisher Indonesia, 2025)
The Siak Sri Indrapura Palace is one of the most important historical relics of the largest Islamic Malay Kingdom in Riau. Built in the late 19th century, this palace is not only the center of government and the official residence of the Sultan of Siak, but also a symbol of glory, architectural richness, and a center for preserving Malay culture. This article reviews the history, architecture, function, and role of the Siak Palace in preserving cultural heritage. The method used in this journal is the library research method. This method involves collecting, analyzing, and synthesizing information from various written sources, such as history books, scientific articles, official documents, and relevant online sources regarding the Siak Sri Indrapura Palace.